2016
DOI: 10.1002/chem.201602916
|View full text |Cite
|
Sign up to set email alerts
|

Rim, Side Arms, and Cavity: Three Sites for the Recognition of Anions by Tetraazolium Resorcinarene Cavitands

Abstract: Two tetrabenzoimidazolium-resorcinarene cavitands were prepared and used for the recognition of chloride, bromide, iodide, cyanide, nitrate, perchlorate, hexanoate, benzenesulfonate, and p-toluenesulfonate. Binding affinities of the two cavitands were determined by H NMR titration and computational analysis. The observed spectral changes were related to specific interaction sites, which were supported by the computational studies. In the case of the C2-H tetrabenzoimidazolium-resorcinarene, the recognition reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 60 publications
1
1
0
Order By: Relevance
“…In addition, the use of the two hosts with the two different relatively rigid spacers should provide interesting information about the influence of the separation of the two pincers on the binding properties of the receptors. The design of these pincer-tweezer anion receptors connects well with our previous studies on the synthesis of molecular tweezers [52][53][54][55][56] and azolium-based anion receptors [57][58][59][60]. The present study describes the use of these two tetraimidazolium-based molecular tweezers as receptors for a selection of three anion guests (Cl À , Br À and I À ).…”
Section: Introductionsupporting
confidence: 73%
“…In addition, the use of the two hosts with the two different relatively rigid spacers should provide interesting information about the influence of the separation of the two pincers on the binding properties of the receptors. The design of these pincer-tweezer anion receptors connects well with our previous studies on the synthesis of molecular tweezers [52][53][54][55][56] and azolium-based anion receptors [57][58][59][60]. The present study describes the use of these two tetraimidazolium-based molecular tweezers as receptors for a selection of three anion guests (Cl À , Br À and I À ).…”
Section: Introductionsupporting
confidence: 73%
“…Theoretical analysis is nowadays indispensable to acquire a deeper understanding at a molecular level of catalytic processes. , However, few theoretical studies of the rate acceleration by supramolecular hosts have been reported. Some examples are cycloaddition inside cucurbit[6]­uril , and inside Rebek’s capsule and Diels–Alder reactions inside β-cyclodextrin (β-CD) and in Rebek’s “softball”, among others. For metallocages, and more particular for the case of the Raymond [Ga 4 L 6 ] 12– metallocage, the orthoformate hydrolysis and aza-Cope rearrangement have been theoretically investigated; in a recent work by Vaissier-Welborn and Head-Gordon the effect of the overall charge of the [M 4 L 6 ] metallocage on the C–C reductive elimination process (by comparing [Ga 4 L 6 ] 12– with [Si 4 L 6 ] 8– , respectively) was also computationally investigated. Most of these works concluded that the electrostatic environment is essential for increasing the reaction rate.…”
Section: Introductionmentioning
confidence: 99%